2007
DOI: 10.1257/jep.21.3.105
|View full text |Cite
|
Sign up to set email alerts
|

Firms in International Trade

Abstract: Since the mid-1990s, researchers have used micro datasets to study countries' production and trade at the firm level and have found that exporting firms differ substantially from firms that solely serve the domestic market. Across a wide range of countries and industries, exporting firms have been shown to be larger, more productive, more skill- and capital-intensive, and to pay higher wages than nonexporting firms. These differences exist even before exporting begins and have important consequences for evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

96
1,183
8
26

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,870 publications
(1,313 citation statements)
references
References 41 publications
96
1,183
8
26
Order By: Relevance
“…A higher value of b i is associated to a higher mean, but leaves the coefficient of variation constant. 6 A higher value of β comes with a lower coefficient of variation. 6 The mean is biβ/ (β − 1) , the standard deviation is bi √ β/ (β − 1) √ β − 2 and the coefficient of variation…”
Section: Preferences Are Given Bymentioning
confidence: 99%
“…A higher value of b i is associated to a higher mean, but leaves the coefficient of variation constant. 6 A higher value of β comes with a lower coefficient of variation. 6 The mean is biβ/ (β − 1) , the standard deviation is bi √ β/ (β − 1) √ β − 2 and the coefficient of variation…”
Section: Preferences Are Given Bymentioning
confidence: 99%
“…Exports and a resulting increase in competition may stimulate the use of variable pay to give incentives to workers to enhance their productivity (Brown and Heywood 2002;Drago and Heywood 1995). This hypothesis is confirmed by the higher wage premium offered in other countries by exporting firms (Bernard et al 2007), and furthermore, it is at least partially verified for the Italian economy because the coefficient associated with exposure to international markets is positive and significant at the 10% level. Unexpectedly, with respect to innovation, we found that firms that declared themselves to have undertaken product and process innovation in the three years before the survey did not show a higher probability of adopting VP agreements, which reveals an impasse in trends towards the implementation of strategies that are devoted to enhancing organisational flexibility; these trends emerged in Italy from similar studies in the 1980s (Biagioli and Curatolo, 1989).…”
Section: Control Variablesmentioning
confidence: 74%
“…In addition, in conformity with related studies, we introduce the sector and firm size (Brown, 1990), firms' geographical locations and export strategies (as in the literature reviewed by Bernard et al 2007), the presence of unions (Black and Linch, 2001), and training (Gielen, 2011). Finally, we consider technology and innovation that may significantly influence workplace organisation, as shown in Bresnahan, Brynjolfsson and Hitt (2002).…”
Section: Incentives and Entrepreneurshipmentioning
confidence: 96%
“…Bernard et al [16] suggest that our understanding of international trade in terms of the origins and implications would be enriched if researchers shift their focus of international trade from countries and industries toward firms and products. Along these lines, Bernard, et al [17] and Melitz and Ottaviano [18] propose models in which the profit margin is endogenous and decreases as import competition intensifies following reductions in trade costs.…”
Section: International Tradementioning
confidence: 99%